Political Economy of Low Greenhouse Gas Emission Dairy Development in Kenya and Tanzania (Greening Livestock) - Socio-economic survey - Crane, Todd; Kihoro, Esther; Vernooij, Vera; Hawkins, James (2024)
Project: Political Economy of Low Greenhouse Gas Emission Dairy Development in Kenya and Tanzania. The objective of this survey was to investigate incentive based interventions for reducing the climate impact of livestock in Kenya and Tanzania. Surveys were conducted in 350 dairy keeping households in Kenya and 350 in Tanzania. These data on dairy production practices, marketing strategies, milk production and prices can be used to enhance dairy development in both countries.